Ответы и объяснения

Лучший Ответ!
2011-12-16T14:04:53+04:00

1) (x+5)*(x+5)=(x-5)*(x-5)

x^2+10x+25=x^2-10x+25

x^2+10x-x^2+10x=25-25 

20x=0

x=0

 

2) (4x+1)*x=(3x-1)*3

4x^2+x=9x-3

4x^2+x-9x+3=0

4x^2-8x+3=0

D= (-8)^2-4*4*3=64-48=16

x1= (8-4)/2*4=4/8=1/2=0,5

x2=(8+4)/2*4=12/8=3/2= 1,5

 

3) (x-4)*x=(10+2x)*2

x^2-4x=20+4x

x^2-4x-20-4x=0

x^2-8x-20=0

x1+x2=8        x1= 10

x1*x2= -20    x2= -2

 

4) (4x+1)*(x+1)= (3x-8)(x-3)

4x^2+4x+x+1=3x^2-9x-8x+24

 4x^2+4x+x+1-3x^2+9x+8x-24=0

x^2+22x-23=0

x1+x2= -22        x1= -23

x1*x2= -23        x2= 1